"Her Life Rests on Your Shoulders": Doing Worry as Emotion Work in the Care of Children With Diabetes. (2nd December 2017) - Watt, Lisa
Research on parents' caregiving experiences in the context of diabetes management have consistently shown that parents experience high levels of pediatric parenting stress, anxiety, depression, and general worry. However, how parents understand their worry is largely unexplored and little attention is paid to the work parents are already actively doing to manage their worry. Adopting Arlie Hochschild's concept of "emotion work" and Dorothy Smith's concept of "work, " this article examines how parents engage in the emotion work of doing worry. Drawing on the analysis of transcribed data from interviews with seven parents caring for children with diabetes, I show how parents expressed worry as an emotion they experience as well as an embodied way of knowing the presence of potential threats to their child's health. Thus, doing worry is an essential aspect of work done by parents to ensure the safety and well-being of their children with diabetes.